2016
DOI: 10.20472/es.2016.5.3.004
|View full text |Cite
|
Sign up to set email alerts
|

Does Gender Diversity in the Boardroom Influence Tobin’s Q of Croatian Listed Firms?

Abstract: Abstract:Gender diversity has attracted attention of scientists

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Conversely, if Tobin’s Q value is lower than 1, it indicates that the stock is under an undervalued condition, which means that management has failed to manage the company’s assets and the potential for low investment growth so that investor interest is low to invest (Campbell and Vera, 2008; Tarigan et al , 2018). The choice of Tobin's Q in our study was motivated, first, by the fact that most prior research on gender diversity had used Tobin's Q as a measure of firm performance (Campbell and Vera, 2008; Carter et al , 2010; Ntim, 2013; Boubaker et al , 2014; Kramaric et al , 2016; Syamsudin et al , 2017; Li and Chen, 2018; Mintah and Schadewitz, 2019; Jiang et al , 2020). Second, Tobin's Q is considered better than other accounting measures, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, if Tobin’s Q value is lower than 1, it indicates that the stock is under an undervalued condition, which means that management has failed to manage the company’s assets and the potential for low investment growth so that investor interest is low to invest (Campbell and Vera, 2008; Tarigan et al , 2018). The choice of Tobin's Q in our study was motivated, first, by the fact that most prior research on gender diversity had used Tobin's Q as a measure of firm performance (Campbell and Vera, 2008; Carter et al , 2010; Ntim, 2013; Boubaker et al , 2014; Kramaric et al , 2016; Syamsudin et al , 2017; Li and Chen, 2018; Mintah and Schadewitz, 2019; Jiang et al , 2020). Second, Tobin's Q is considered better than other accounting measures, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…In other words, Leverage relates to the credit supply and lending in banking and their returns of banks will depend on sensitively on Leverage positions [8]. Research conducted by Kramaric, [9] found that Leverage has a significant positive effect on Firm Value. This result is different from research [10] which states that leverage has no effect on firm value.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of digitization are thus viewed as the fourth industrialization wave, which will fundamentally alter business. Therefore, a company's capacity to tackle the new obstacles brought on by digitalization will determine how long it can remain in operation (Kramaric, 2020). Bancassurance is a component of banks' efforts to diversify their income streams and grow.…”
Section: Introductionmentioning
confidence: 99%